Sistem Pendukung Keputusan Pemilihan Lembaga Bimbingan Belajar Berdasarkan Pendapatan Orang Tua dengan Metode Simple Additive Weighting - Fitri Yanti; Tonni Limbong (Yayasan Kita Menulis, 2020)
Tutoring institutions are non-formal institutions engaged in the world of education. the number of tutoring institutions that have sprung up nowadays, making competition increasingly fierce causing parents to be selective in choosing however. This is what sometimes makes parents confused about choosing a tutoring institution that suits their income, causing breakups in the middle of the road because they are not in accordance with their income. In a decision support system, the application of a method that can be used as a reference for problem solving must be carried out. In this case, the method used is the Simple Additive Weighting Method (SAW) which is one of the methods used in problem solving in Fuzzy Multiple Attribute Decision Making (FMADM).